2020
DOI: 10.3390/ijms21176446
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Transcription Factor Yin Yang 1 and Its Selectively Identified Target Survivin in High-Grade B-Cells Non-Hodgkin Lymphomas: Potential Diagnostic and Therapeutic Targets

Abstract: B-cell non-Hodgkin lymphomas (B-NHLs) are often characterized by the development of resistance to chemotherapeutic drugs and/or relapse. During drug-induced apoptosis, Yin Yang 1 (YY1) transcription factor might modulate the expression of apoptotic regulators genes. The present study was aimed to: (1) examine the potential oncogenic role of YY1 in reversing drug resistance in B-NHLs; and (2) identify YY1 transcriptional target(s) that regulate the apoptotic pathway in B-NHLs. Predictive analyses coupled with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…In cancer, YY1 plays a controversial role [ 25 , 26 , 27 ]. Regarding LC, YY1 has been seen to work as an oncogene, although the mechanism is still not well defined [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, YY1 plays a controversial role [ 25 , 26 , 27 ]. Regarding LC, YY1 has been seen to work as an oncogene, although the mechanism is still not well defined [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that YY1 is highly expressed in many cancers, participates in the regulation of tumor proliferation and growth, and plays a dual role in inhibiting or promoting tumor progression [ 12 ]. For example, YY1 inhibits tumor proliferation in colon cancer and breast cancer [ 14 ] but promotes tumor growth in melanoma, non-Hodgkin Lymphomas [ 15 ], and prostate cancer [ 12 ]. The expression of YY1 is significantly increased in colon cancer and subjected to O-GlcNAcylation modifications, which increases the stability and transcriptional activity of YY1, thus promoting tumor proliferation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The YY1 gene is 23 kb long and is highly conserved across cells; its translated protein consists of 414 amino acids [ 45 , 46 , 47 ]. Due to its roles in the cell cycle, gene expression, DNA repair, cellular metabolism, differentiation, survival, and apoptosis, YY1 is vital in early developmental processes as well as lifelong regulatory processes [ 48 , 49 , 50 ]. However, it has also been found that YY1 is overexpressed in many types of cancers, specifically in several metastatic cancers [ 51 , 52 , 53 , 54 ].…”
Section: Yy1 Overexpression In Cancer Oncogenic and Immunosuppressive...mentioning
confidence: 99%